1978
DOI: 10.1152/ajprenal.1978.235.4.f345
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between blood pH and potassium and phosphorus during acute metabolic acidosis

Abstract: Metabolic acidosis is known to be associated with increased blood potassium and phosphorus concentrations but the influence of mineral versus nonmineral acids on these variables remains undefined. Therefore, we infused anesthetized mongrel dogs with 0.45% saline (controls), the mineral acids HCl and NH4Cl, and the nonmineral acids lactic, beta-hydroxybutyric and methyl malonic for 1-3 h. Administration of both mineral acids was associated with significant increases in plasma potassium. In contrast, infusion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
1

Year Published

1979
1979
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 0 publications
3
28
1
1
Order By: Relevance
“…It was found that the presence of d ‐lactataemia in acidemic calves resulted in significantly lower odds for hyperkalemia but significantly higher odds for the presence of hypokalemia 8. This is in line with the results of experimental studies which reported that a hyperkalemic state can be induced by infusions with inorganic acids such as HCl or ammonium chloride but not if organic acids such as lactic acid, acetic acid or ß‐hydroxybutyrate are infused 24, 25, 26. This disparate effect on K + homeostasis was related to intracellular moving of organic anions which is believed to result in a higher degree of intracellular acidosis and Na + loading and consequently a higher Na + /K + ‐ATPase activity resulting in a net cellular uptake of potassium ions 27.…”
Section: Discussionsupporting
confidence: 78%
“…It was found that the presence of d ‐lactataemia in acidemic calves resulted in significantly lower odds for hyperkalemia but significantly higher odds for the presence of hypokalemia 8. This is in line with the results of experimental studies which reported that a hyperkalemic state can be induced by infusions with inorganic acids such as HCl or ammonium chloride but not if organic acids such as lactic acid, acetic acid or ß‐hydroxybutyrate are infused 24, 25, 26. This disparate effect on K + homeostasis was related to intracellular moving of organic anions which is believed to result in a higher degree of intracellular acidosis and Na + loading and consequently a higher Na + /K + ‐ATPase activity resulting in a net cellular uptake of potassium ions 27.…”
Section: Discussionsupporting
confidence: 78%
“…Fluxes of potassium among the fluid compartments were previously thought to be solely determined by changes in acidity. Other factors, however, have been identified as modulators of the plasma potassium response (5); prominent among them is the nature of the anion escorting the protons responsible for acidemia (6)(7)(8)(9). In sharp contrast with mineral acid acidosis that consistently leads to hyperkalemia, acute organic acid acidosis is not associated with a significant increase in plasma potassium (10).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is even difficult to interpret the studies in dogs with clarity. Either severe hyperkalemia (1,28) or an unchanged plasma [K ϩ ] (29) were reported during post-IV HCl equilibration periods using arterial plasma samples.…”
Section: Discussionmentioning
confidence: 99%